Avaliação dos mecanismos resistentes ao cisalhamento em concreto armado sem armadura transversal - Samora, Mario Sergio (2015)
The safety fundamental principle of reinforced concrete structures related of a possible collapse is that the security does not depend on the concrete resistance tensile strength to eliminate the risk of collapse without notice. The cracking caused by tensile stresses can affect the concrete structure and should be avoided to the natural structural collapse doesn t occur. The diagonal crack that appears on the act of breaking is called critical crack, characteristic of shear failure. In this work were experimentally studied the additional mechanisms from the shear resistant trusses in reinforced concrete frames without transverse reinforcement. The experimental experiments consists on testing eight frames that were subjected to a simple bending. Two concrete grades of characteristic the compressive strength were considered on the construction of the frames. To resist the bending stresses, the frame s beams are designed in the field 3 of the ultimate limit states. Different rates and diameters of longitudinal reinforcement were used. In all frames weren t considered the use of transverse reinforcement in the region of shear on the beams. From the results obtained were analyzed the proposed criteria to define the portion of the contribution for the shear resistance mechanisms of concrete without the use of transverse reinforcement and the influence of the concrete resistance and longitudinal reinforcement rates in the numerical results experimentally obtained.